3PC-021 Storage of nivolumab pembrolizumab and daratumumab for 14 days after compounding in the hospital pharmacy: a microbiological stability study. (24th March 2020) - Cancanelli, L; Selmin, F; Camuffo, L; Mangoni, G; Piccoli, M; Rivano, M; Cilurzo, F; Minghetti, P
Abstract : Background and importance: Viable microorganisms and/or endotoxins administered parenterally via contaminated preparations may lead to nosocomial infections, SIRS/sepsis and increased mortality of patients. The pharmacist has the responsibility to ensure that the product is stable in the final administered preparation. Aim and objectives: To verify if monoclonal antibodies such as nivolumab, pembrolizumab and daratumumab are promoters or inhibitors of microbial growth. Moreover, the microbiological stability of dilutions at clinically relevant concentrations were verified over a 14 day period. Material and methods: Samples, reconstituted according to the summary of product characteristics (SPC) in 1 mL syringes, were injected into standardised suspensions of Pseudomonas aeruginosa, Staphylococcus aureus and Candida albicans . 1 At different time points (ie, 0, 1, 3, 5, 24, 48 and 144 hours) an aliquot of 0.01 mL, containing about 100 CFU, was transferred to the trypticase soy agar plate and sabouraud dextrose agar+chloramphenicol plate. After 24 hours of incubation at 37°C, samples were assayed. Moreover, a total of 24 syringes were stored for 1, 3, 6, 7, 10 and 14 days before being incubated to determine microbiological stability according to the EP method. Results: The results showed that 144 hours after inoculation no colony forming units were detected for the C albicans and S aureus strains. The only microorganism that survived after 5 days was P aeruginosa . Comparing the control with the samples analysed, no significant growth or reduction in microorganisms were observed. The samples were all clear after 14 days of incubation. Conclusion and relevance: Compared with the control, no significant growth or reduction in microorganisms were observed, indicating that the monoclonal antibodies investigated cannot be used by the strains as substrates for their survival. It can also be deduced that these monoclonal antibodies have no bactericidal or bacteriostatic actions. Under these conditions, the monoclonal antibodies were microbiologically stable for 14 days. In conclusion, when data on 'in use' stability' are available for a period of 14 days, a new model of patient management in the day hospital and drug preparation in the hospital pharmacy could be organised. References and/or acknowledgements: 1. Sarakbi I, Federici M, Krämer I. Viability of microorganisms in novel chemical and biopharmaceutical anticancer drug solutions. EJPPS 2015;20:5–12. No conflict of interest.